Anion gap‐opening metabolic acidosis and urinary findings in the early diagnosis of ethylene glycol poisoning: A case report. Issue 1 (7th January 2022) - Ukita, Kentaro; Otomune, Kanako; Fujimoto, Ryo; Hasegawa, Kanako; Izumikawa, Koichi; Morimoto, Nobutoshi; Sasaki, Kazuhiro; Hirasaki, Akihito; Takaguchi, Koichi
Abstract: Causative agent identification is important in the treatment of poisoning. We report the case of a patient who presented with an altered level of consciousness after drinking a fluorescent pink liquid. Upon measuring the anion gap and urinary calcium oxalate level, the patient was diagnosed with early ethylene glycol poisoning. Abstract : Ethylene glycol poisoning was difficult to measure immediately in the blood. The diagnosis can be made by detecting anion gap‐opening metabolic acidosis and calcium oxalate crystals in the urine, which can be measured in many medical institutions.